Pendekatan Rational Choice Pada Reformasi Ekonomi (Doi Moi) Di Vietnam - Dewi, Nevy Rusmarina (State Islamic Institute of Kudus (IAIN Kudus), 2018)
The development of world globalization after the end of the Cold War made many countries in the world adapt to the changes in the existing world constellation. The countries that were most affected were those who supported the Eastern Bloc with communist ideology. Some countries in Asia with communist ideology, such as China, Vietnam, and Laos, have had to face such rapid changes in the world. The conflict between maintaining ideology by adopting the values of globalization is a very important issue. China strives not to be trapped in the entanglement of the globalization of the world by changing the pattern of thinking for the achievement of its economy through economic reform. Economic reform by opening up the economy in welcoming world free trade to take advantage of world trade, but still maintaining communist ideology is the solution for China. China's success in its economic reforms was taken into consideration for Vietnam, its communist ally, to adopt the same steps. With very bad economic conditions after the end of the Vietnam War and its limitations in carrying out reconstruction, real action was greatly needed by Vietnam amid the end of dependence on the Soviet Union. The economic reform movement through